一株耐盐且高效降解没食子酸的肺炎克雷伯氏菌及其应用 (2024)
本发明涉及没食子酸降解技术领域，公开了一株耐盐且高效降解没食子酸的肺炎克雷伯氏菌及其应用。所述肺炎克雷伯氏菌命名为MSZS12，已在2021年10月25日保藏于中国微生物菌种保藏管理委员会普通微生物中心，保藏编号为CGMCC NO.23660，微生物分类命名为肺炎克雷伯氏菌肺炎亚种Klebsiella pneumoniae subsp.pneumoniae。本发明的菌株MSZS12能够以没食子酸为唯一碳源，高效降解没食子酸，并能适应较宽的pH范围和较高的NaCl浓度，且耐盐性和对没食子酸的分解能力具有较好的传代稳定性，在含没食子酸废水的生化处理中具有较好的应用前景。 The invention relates to the technical field of gallic acid degradation, and discloses a salt-tolerant klebsiella pneumoniae capable of efficiently degrading gallic acid and application of the klebsiella pneumoniae. The Klebsiella pneumoniae is named as MSZS12, is preserved in the China General Microbiological Culture Collection Center on October 25, 2021, and has the preservation number of CGMCC NO.23660, and the microorganism classification is named as Klebsiella pneumoniae subsp.pneumonae, and the Klebsiella pneumoniae subsp.pneumonae is named as Klebsiella pneumoniae subsp.pneumonae. The strain MSZS12 disclosed by the invention can efficiently degrade gallic acid by taking gallic acid as a unique carbon source, can adapt to